Kanban food ordering system - Andi Razif, Andi Rahim (2015)
The emergence and the growth of mobile devices and wireless technologies in this era has created a great impact to our lives especially in business industries. This project aims to implement these technology to restaurant business industries. This paper discussed the designs and implementations of a customizable wireless food ordering system, “Kanban Food Ordering System (KanbanFOS)”. Currently, most restaurants are still using the traditional techniques of order taking and management. The traditional techniques of order taking and managements was entirely a manual process which is simple yet has numerous downsides. Some of the downsides are, the order taken are not in sequences and the traditional technique is prone to human errors. The objectives of this project are to study the development of mobile-based applications and wireless technology, to develop a wireless food ordering system for the use of restaurants and to test the functionality of the system based on its scopes. The system contains three main modules which are Waiter Module, Kitchen Module and Admin Module. Each of these modules are developed specifically for different types of users, which are Waiters, Kitchen Staff/Chef and Admin/Cashier. Rapid Application Development (RAD) Cycle methodology has been chosen as the software development methodology for this project. The end product of this project has been developed and tested in real situations. The end product has fulfilled the objective of this project and has been distributed to the clients.